CDIO-based teaching at universities: A case study for students majoring in electrical and electronic engineering technology, Vietnam - Hong, Hoang Thi; Hung, Tran Van; Vu, Nguyen Quoc; Thao, Dinh Thi Thanh; Hung, Do The (Journal of Education and e-Learning Research, 2024)
In the 1980s of the twentieth century, universities in developed countries began to realize the growing gap between the capabilities of new graduate engineers and the actual requirements of engineering branches. The strong progress of technology requires engineers to have the intellectual abilities and necessary job-specific skills to master that progress. This paper focuses on Conceive, Design, Implement and Operate (CDIO) approach-based teaching for students majoring in electrical and electronic engineering technology at engineering universities in Vietnam to demonstrate the feasibility of the teaching model. The experimental method of synthesizing qualitative and quantitative results for 90 students in control and experimental classes was used. The experimental and control classes both had 45 students. SPSS software version 22 was used to gather data and evaluate the learning results of the two experimental and control groups. According to the findings of the T-test analysis of the independent variables for the two groups, the experimental class performed better in academics and had students in the experimental group who were more satisfied with their post-test scores. This result contributes to confirm that the use of the CDIO-based teaching model in Vietnam is effective for students majoring in electrical and electronic engineering technology.